TỔNG HỢP CAO SU THIÊN NHIÊN LỎNG CÓ NHÓM HYDROXYL CUỐI MẠCH BẰNG PHƯƠNG PHÁP FENTON QUANG HOÁ - Hữu Lý, Phạm; Thị Bích Thanh, Đỗ; Thúy Hồng, Kim; Quang Tuấn, Lê; Tùng Sơn, Phạm; Đức Giang, Lê (Vietnam Journal of Science and Technology, 2017)
Hydroxyl-terminated  liquid  natural  rubbers  (HTLNRs)  prepared  by  the  photo  Fenton reaction have been characterised by 1H-NMR, 13C-NMR, DEPT, FTIR and UV-Vis. The results showed  that HTLNRs  had  hydroxyl  end  groups  at  both  chain  ends  and  the  configuration  of HTLNRs macromolecules had been maintained as  that of  the virgin natural  rubber  (NR) ones. The  photo  degradation  reaction  mechanism  of  the  NR  with  photo  Fention  reagents  to  form HTLNR was also proposed and discussed